2022
DOI: 10.1093/braincomms/fcac238
|View full text |Cite
|
Sign up to set email alerts
|

Reduced RNA adenosine-to-inosine editing in hippocampus vasculature associated with Alzheimer’s disease

Abstract: Alzheimer’s disease is the most common form of dementia and recent studies identify a type 1 interferon response in Alzheimer’s disease possibly driving neuro-inflammation and other Alzheimer’s disease pathologies. Loss of adenosine-to-inosine editing of endogenous Alu RNAs results in accumulation of Alu double-stranded RNAs, activation of double-stranded RNA sensors, and induction of interferon and nuclear factor kappa B regulated genes. Here, we investigated if changes in adenosine-to-inosine editing were as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…Interestingly, in both sub-GRNs, the number of TGs that each TF controls varies to an important degree, exhibiting a scale-free like topology. The analysis of the top-10 TFs controlling the highest number of TGs, has revealed that most of these TFs have been found associated to Alzheimer disease in previous studies [ 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 ], as reported in Table 4 . The full lists of TFs belonging to both communities are reported in Table A1 .…”
Section: Resultsmentioning
confidence: 92%
“…Interestingly, in both sub-GRNs, the number of TGs that each TF controls varies to an important degree, exhibiting a scale-free like topology. The analysis of the top-10 TFs controlling the highest number of TGs, has revealed that most of these TFs have been found associated to Alzheimer disease in previous studies [ 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 ], as reported in Table 4 . The full lists of TFs belonging to both communities are reported in Table A1 .…”
Section: Resultsmentioning
confidence: 92%
“…Conversely, ADARB1 + neurons are our only population not previously identified among AD vulnerable neurons. However, reduction in ADARB1 expression is associated with AD 58 . On the other hand, we do not find a significant reduction in total number of other neuronal subpopulations previously identified as vulnerable in AD, such as CUX2 + , PCP4 + , GPC5 + and SST + neurons 7,35,47 .…”
Section: Discussionmentioning
confidence: 98%